Stammzellforschung. Debatte zwischen Ethik, Politik und Gesellschaft - Albrecht, Stephan; Dierken, Jörg; Freese, Harald; Hößle, Corinna (Hamburg University Press, 2003)
The biopolitical debate on stem cell research and reproductive medicine has provoked heated controversy over biological issues and related anthropological questions. The social implications of the controversial issues are no less controversial: To what extent are developments in molecular genetics and reproductive medicine changing our normative orientations? What role do politics and law play in relation to science and economics? And how do biotechnological innovations shape ethical discourses? The contributions of the volume address such questions. They offer information and assessments from medical and scientific perspectives and contain normative and cultural studies reflections from pedagogy, philosophy and theology. The volume is the result of a multidisciplinary lecture series that took place in the summer semester 2002 at the University of Hamburg.